White Revolution in India: What smallholders can do given the right ecosystem - Ashok Gulati; Ritika Juneja (University of Bonn, Center for Development Research (ZEF), 2023)
The key objective of this paper is to demonstrate what smallholders can do in the dairy sector given the right ecosystem. India's story of the "white revolution" is a story that can inspire millions in smallholder economies. It has important lessons in terms of government policies that supported and encouraged institutional innovation, infusion of new technologies all along the value chains, and reducing the risk in marketing of milk by smallholders. India's livestock sector operates on a low-input, high-output model and is sustained by millions of farmers who have an average herd size of less than four animals. India has come a long way from being a milk-deficit country in the 1950s and 1960s to a self-sufficient one with some surplus. The value of milk produced in India today is more than the aggregate value of paddy, wheat, pulses and sugarcane in 2020-2021. The transformation in the milk sector was initially backed by the government through the Operation Flood (OF) program which helped in setting up dairy cooperatives across the country, facilitating collection of milk from millions of dairy farmers to be delivered to processing plants and distributing pasteurized and homogenized milk through thousands of retail outlets in urban cities. Following OF, it was realized that India needed a "double engine force" to boost the dairy sector to meet growing demand of milk in the cities. In 1992, an initial attempt was made to liberalize the dairy sector and open it up to organized private sector players. However, full-scale liberalization only took place a decade later in 2002-03 under the Atal Bihari Vajpayee government, when almost all restrictions related to capacity of private companies to enter the dairy sector were removed and the industry was completely de-licensed. As a result, many private companies began to emerge across the country and procurement volumes were matched within a few years. By 2020-2021, organized private companies procured a slightly larger share of milk directly from the farmers than the dairy cooperatives. As a result of this "double engine" growth, India produced 221 million metric tons (MMT) of milk in 2022, making it by far the world's largest milk producing country - followed by the US, with 102 MMT. Collectively, the EU countries produce about 155 MMT. India's per capita availability of milk has also gradually improved over the years from 130 grams per day in 1950-51 to 427 grams per day in 2020- 2021. However, dairy farmers continue to face some serious challenges that need to be addressed for a sustainable and efficient growth of India's dairy sector. The large size of the bovine population (more than 300 million) often creates a shortage of feed and fodder for milk cattle. Poor nutrition of animals results not only in lower milk yields, but also exposes them to diseases, like mastitis. Having a large bovine population also has an environmental cost due to the associated high greenhouse gas (GHG) emissions. According to Government of India (GoI) data, 55% of the total GHG emissions from the agriculture sector comes from livestock. One of the reasons behind high methane emissions amongst dairy animals is lack of a balanced diet and poor nutrition. The GoI and private dairy companies have been spearheading many innovations and technologies in recent years to help overcome these challenges. Some of the technologies gaining popularity in the past few years include assisted reproduction technologies (sex sorted semen), green fodder hydroponics, development of hybrid fodder and utilizing the internet of things for herd management. These innovations and technologies aim to make the dairy value chain more efficient and help smallholder farms by ensuring that production costs are minimized as milk yields increase.
Keywords: 330